Potret Inovasi Tata Kelola Perekaman Data dan Dokumen - Maruapey, Muhammad Husein (Jurnal Administrasi Publik (Public Administration Journal), 2019)
Managing population data involves many complex activities from various types of organizations, stakeholders, and knowledge. Innovation is very important in increasing the efficiency of the public sector. Once the importance of innovation governance will have consequences for the failure or success of the innovation itself. Good governance of innovation is a reflection of the strategy of a process whose benefits can be felt well. The focus of this research is the investigation of the phenomenon of management of innovation in the data management and population documents sector in Southeast Aceh Regency. Furthermore, it is compared with several regions which also manage population data and documents innovatively. Qualitative methods with phenomenological analysis are used to explain and identify how the phenomenon occurs. Data collection is done inductively, interviews, discussions and observation of participation. Triangulation is used to draw conclusions on empirical data and secondary data. The results of this study found that the management of innovation must be supported by various supporting policies, apart from the capacity of the leader as the executor. Community participation, cross-border collaboration also contributes to positive support. Innovation is also an urgent need now to deliver good and competitive public services by the government.